Re : Thinking Europe: Thoughts on Europe: Past, Present and Future - Albrecht, Yoeri; Segers, Mathieu (Amsterdam University Press, 2016)
What is Europe? This concise, yet immensely complex, question, more pressing than ever during this time of intense political crisis-the worst since the process of European integration began in the 1950s-sets the stage for this volume. Bringing together international thinkers and scholars from different generations, including Barack Obama, Margaret Thatcher, Milan Kundera, Tom Holland, Ivan Krastev, Philipp Blom, and many others, the essays engage with the paradoxes and puzzles of European identity, ultimately rethinking the continent's culture, history, present-and future.